Thermal performance prediction of outdoor swimming pools. (August 2019) - Lovell, D.; Rickerby, T.; Vandereydt, B.; Do, L.; Wang, X.; Srinivasan, K.; Chua, H.T.
Abstract: The sizing of water heating plants for outdoor community swimming pools conventionally relies on empirical methods and industry guidelines that seldom account for local climatic conditions. In the absence of a model that accounts for all modes of heat and mass transfer, the prediction of water temperature of an outdoor pool and hence the sizing of the heating plant can result in either significant over or under estimation which could impact on not only capital and operating costs but also on complying with environmental accountability and control strategy. The model developed herein accounts for numerous contributors to the thermal energy balance of pool water, notable among them being free and forced convection heat and mass transfer to/from pool and radiation cooling to the sky. Cloud and rain effects are also incorporated into the model. The role of solar and ambient weather conditions is emphasised. The first-principle and analytical model has been calibrated against data from an Olympic sized swimming pool in Perth, Australia. A comparison between various models in the literature shows that the present model is able to replicate experimental data much more closely than others, with 82% of the results being within ±0.5 °C of the actual measured pool temperatures and with 67% of the predicted heating capacities being within ±100 kW of the measured heating capacities. Graphical abstract: Image 1 Highlights: Free convection and evaporation is important to outdoor swimming pool performance. Our study is benchmarked against 27 months of data from an Olympic swimming pool. 82% of our model prediction is within ±0.5 °C of the actual pool temperature. 67% of our model prediction is within ±100 kW of the actual pool heating capacity.